Gaseous and electrochemical hydrogen storage behaviors of nanocrystalline and amorphous Nd-added Mg2Ni-type alloys - Zhang, Yang-Huan; Liu, Sheng-Long; Yang, Tai; Zhang, Guo-Fang; Li, Xia; Zhao, Dong-Liang (Rare metals, 2015)
Melt spinning technology was used to prepare the Mg2Ni-type(Mg24Ni10Cu2)100-xNdx(x = 0, 5, 10, 15,20) alloys in order to obtain a nanocrystalline and amorphous structure.The effects of the spinning rate on the structures and gaseous and electrochemical hydrogen storage behaviors of the alloys were investigated.The analysis of X-ray diffraction(XRD), transmission electron microscope(TEM), and scanning electron microscope(SEM) linked with energy-dispersive spectroscopy(EDS)reveals that all the as-cast alloys hold a multiphase structure, involving the main phase Mg2 Ni and some secondary phases such as Mg6 Ni, Nd5Mg41, and Nd Ni.The as-spun Nd-free alloy displays an entire nanocrystalline structure,whereas the as-spun Nd-added alloys hold a nanocrystalline and amorphous structure, and the amorphization degree visibly increases with the spinning rate increasing.The melt spinning ameliorates the hydrogen storage performances of the alloys dramatically.When the spinning rate rises from 0(the as-cast was defined as the spinning rate of 0 m s-1) to 40 m s-1, the discharge capacity increases from 86.4 to 452.8 m Ah g-1, the S20(the capacity maintain rate at 20 th cycle) value increases from53.2 % to 89.7 %, the hydrogen absorption saturation ratio(Ra5, a ratio of the hydrogen absorption quantity in 5 min to the saturated hydrogen absorption capacity) increases from36.9 % to 91.5 %, and the hydrogen desorption ratio(Rd10,a ratio of the hydrogen desorption quantity in 10 min to the saturated hydrogen absorption capacity) increases from16.4 % to 47.7 % for the(x = 10) alloy, respectively.